Analysis Of The Influence of Leadership, Work Motivation and Job Satisfaction On Employee Performance at @Nlangit Mobil Official - Muhammad Azwari; Muhammad Toyib daulay; Darmilisani (CV. Doki Course and Training, 2026)
Human resource development (HR) is a strategic factor in improving the performance of public sector This research aims to analyze the influence of leadership, work motivation, and job satisfaction on employee performance at @Nlangit Mobil Official. Employee performance is an important factor in supporting the success and competitiveness of organizations, especially in the automotive service sector that demands high service quality and productivity. This study uses a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to employees of @Nlangit Mobil Official and analyzed using statistical analysis techniques. The results of the study indicate that leadership and work motivation have a positive and significant effect on employee performance. In addition, job satisfaction also positively influences employee performance and is affected by leadership and work motivation. These findings indicate that the implementation of effective leadership, enhancement of work motivation, and creation of good job satisfaction can optimally improve employee performance. This research is expected to provide practical contributions to management in human resource management.